Crystallization and X-ray diffraction analysis of human CLEC-2. - Watson, A; O'Callaghan, C (2005)
The human C-type lectin-like protein CLEC-2 has recently been shown to be expressed on the surface of platelets and to function as a receptor for the snake-venom protein rhodocytin. The C-type lectin-like domain (CTLD) of CLEC-2 was expressed in Escherichia coli, refolded and purified. Crystals of this recombinant CLEC-2 were grown by sitting-drop vapour diffusion using polyethylene glycol (PEG) 6000 as a precipitant. After optimization, crystals were grown which diffracted to 2.0 A using in-house radiation (lambda = 1.5418 A). These crystals belonged to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 35.407, b = 55.143, c = 56.078 A. The presence of one molecule per asymmetric unit is consistent with a crystal volume per unit weight (VM) of 1.82 A3 Da(-1) and a solvent content of 32.6%. These results suggest that crystals producing diffraction of this quality will be suitable for the structural determination of human CLEC-2.